Prevalence of chronic kidney disease in patients with metabolic syndrome: a single centre experience in Nigeria - Egbi, Oghenekaro Godwin; Unuigbe, Evelyn; Oviasu, Efosa (African Journal of Nephrology, 2014)
<p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Background:The prevalence of metabolic syndrome (MS) is increasing worldwide, not sparing developing countries like Nigeria.Chronic kidney disease (CKD) is also assuming epidemic proportions globally. Metabolic syndrome has been associatedwith CKD in several reports, most of which are foreign based. Given that data on CKD in MS patients is rare in thispart of the world, the study was undertaken with the aim of determining the prevalence of CKD in patients with MS. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Methods:Two hundred and twenty two subjects completed the study out of the two hundred and thirty that met the criteria forMS as defined by the harmonized criteria for definition of MS. CKD was defined as eGFR less than 60 ml/min/1.73m2 as determined by the Modification of Diet for Renal Disease (MDRD) formula. Proteinuria was defined as presenceof at least 1+ of protein in urine in absence of leukocyturia or nitrituria. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Results: Elevated blood pressure, elevated fasting glucose and central obesity were the commonest traits of MS. The prevalenceof CKD in participants with MS was 20.3% while proteinuria was found in 121(54.5%) of them. The prevalence ofCKD increased with additional traits of the syndrome. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Conclusion:CKD and proteinuria are prevalent in patients with metabolic syndrome. Prevalence of CKD in MS increases with additional component of the syndrome.